Governar a humanidade na guerra e na paz: uma genealogia das organizações não governamentais de direitos humanos na segurança internacional - Duarte, João Paulo Gusmão Pinheiro (2019)
The present research aims to analyze the governmental activity exerted by non- governmental organizations that promotes of human rights in the normative conformation of international security. Activity that is made explicit in the emergence of planetary governmentality, programmatic in which it is possible to observe the expansion of the instruments directed at the regulation of war, by the dissemination of dispositives oriented to the control of violence; i. e., the resizing of the security aim at the States in the security of humanity and the planet. Using the genealogical method proposed by Michel Foucault, the research shows proveniences and the emergence, in the midst of the dynamics of war and peace, of the governmental operation of large and representative non-governmental organizations of human rights, to then indicate and problematize such engagement as a vector which articulates and disposes not only the control of international relations, but also the control of human life, on a scale that goes beyond the limitations of sovereignty to directed to the global set of humanity